Profile of Peanut Spesific-IgE in Atopic Dermatitis - L, Indiarsa Arief; Lumintang, Hans; Ervianti, Evy (Faculty Of Medicine Airlangga University, 2014)
Background : Atopic Dermatitis (AD) is a chronic reccurent disease. One of the environmental factors which possibly involved in the reccurency of AD is food allergy such as peanut. Peanut allergy in the pathogenesis of AD is by induction IgE and T cells. Peanut-spesific IgE allergen are observed in AD patient. Purpose: To identify the distibution of serum IgE concerning the peanut antigens according to AD. Methods:This trial was cross sectional descriptive study, which studied 33 atopic dermatitis patients, which fulfill inclution criterias.We describe the anamnesis, physical examination, peanut-spesific IgEÂ and the severity of AD using SCORAD index. Results: There were 7 patients (21,2%) with positive result of peanut-spesific IgE. The positive result of peanut-spesific IgE were noted most often on AD patients who suffer from severe grade of AD severity score (85,7%) but not found in class 3 or more (where antibody can detect significanly, often clinical manifestasion appeared when had sensitisation). Conclusion: The positive result of peanut-spesific IgE class 1 (0,35- 0,7 IU/mL)Â 5 people (15,1%) andÂ class 2 (0,7-3,5 IU/mL) 2 people (6,1%) were noted most often on AD patients who suffer from severe grade of AD severity scoreKey words: atopic dermatitis, peanut-spesific IgE.